Colorectal Cancer Screening and Computerized Tomographic Colonography A Comprehensive Overview - Cash, Brooks D.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Colorectal Cancer Screening and Computerized Tomographic Colonography: A Comprehensive Overview is an authoritative volume on CT colonography. Structured in a manner that will allow the reader to understand the practical and larger public health issues surrounding both CT colonography and CRC screening in general, the text is designed to reach a broad audience of specialist clinicians and primary care physicians. The book provides an overview of the disease and risk factors of colorectal cancer, as well as the history and development of CTC as both a colorectal imaging and screening modality. The text also reviews the controversies, potential pitfalls, and exciting new directions and capabilities inherent in the practice of CTC. Filled with high quality images and authored by experts in the field, Colorectal Cancer Screening and Computerized Tomographic Colonography: A Comprehensive Overview is the definitive reference for clinicians interested in computerized tomographic colonography and CRC screening.
Overview of Colorectal Cancer -- Colorectal Cancer Screening Tests and Recommendations -- CTC Background and Development -- Indications and Evidence for CTC -- Performance and Interpretation of CTC -- Integration of CTC into a CRC Screening Program -- CTC Controversies (Radiation exposure, Extracolonic findings, Cost-effectiveness) -- CTC Pitfalls/Limitations -- Future Directions/Innovations with CTC (Prepless CTC, Alternative displays, Computer aided detection).
Keywords: Medicine; Radiology, Medical; Gastroenterology; Emergency medicine; Medicine & Public Health; Gastroenterology; Imaging / Radiology; Primary Care Medicine